2023
DOI: 10.1111/jcmm.17651
|View full text |Cite
|
Sign up to set email alerts
|

The application of nanopore targeted sequencing in the diagnosis and antimicrobial treatment guidance of bloodstream infection of febrile neutropenia patients with hematologic disease

Abstract: Traditional microbiological methodology has limited sensitivity, detection range, and turnaround times in diagnosis of bloodstream infection in Febrile Neutropenia (FN) patients. A more rapid and sensitive detection technology is urgently needed.Here we used the newly developed Nanapore targeted sequencing (NTS) to diagnose the pathogens in blood samples. The diagnostic performance (sensitivity, specificity and turnaround time) of NTS detection of 202 blood samples from FN patients with hematologic disease was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Besides that, updating the Super-accurate basecalling algorithm in GridION and improvement of sequencing depth were conducted to ensure the accuracy and reliability of the sequencing data. Until now, several studies have reported using nanopore metagenomic or targeted sequencing for microbial species identification from blood ( Ashikawa et al., 2018 ; Sakai et al., 2019 ; Hong et al., 2023 ). Pathogen identification and related antimicrobial drug resistance genes prediction were conducted from simulated BSI samples ( Zhou et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, updating the Super-accurate basecalling algorithm in GridION and improvement of sequencing depth were conducted to ensure the accuracy and reliability of the sequencing data. Until now, several studies have reported using nanopore metagenomic or targeted sequencing for microbial species identification from blood ( Ashikawa et al., 2018 ; Sakai et al., 2019 ; Hong et al., 2023 ). Pathogen identification and related antimicrobial drug resistance genes prediction were conducted from simulated BSI samples ( Zhou et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sanger sequencing, also known as dideoxy chain-termination sequencing, is a widely used DNA sequencing method developed in the 1970s . This method is still commonly employed for sequencing recombinant DNA constructs and validating variant calls generated by Next-Generation sequencing methods. DNA sequencing is a valuable tool for teaching biochemistry concepts and techniques to university students.…”
Section: Introductionmentioning
confidence: 99%